A TRANSCENDÊNCIA DO POLÍTICO: CONCEDENDO VOZES A ÍPSILONS - Filho, Maurício Fontana; Noll, Felipe Halfen; Tonel, Rodrigo; Neto, Alfredo Copetti (Salão do Conhecimento, 2017)
Projeto de Pesquisa institucional